2017
DOI: 10.1177/0265407517735913
|View full text |Cite
|
Sign up to set email alerts
|

Young female adults’ experiences of their relationships with older people: The Mmogo-method®

Abstract: Most of the intergenerational research in South Africa has been undertaken on African cultures. This study aims to cast light on the experiences of Afrikaans-speaking young female adults in relation to older people, using the Mmogo-method®, a visual projective data collection method. Eighteen young female adults (aged 21–30), all students, were purposefully selected and willingly participated. The four phases of the Mmogo-method were applied, for which participants used unstructured materials, and based on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Gozu (2017) found that young adults who scored highly in terms of openness, conscientiousness and agreeableness, and low on neuroticism, were more likely to report having better relationships with their siblings. Finally, in a qualitative study, Roos et al (2019) found that perceptions of grandparents' personality (e.g., empathetic vs. rigid) influenced whether young adult women desired closeness with, or distance from, their grandparents.…”
Section: Individual Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gozu (2017) found that young adults who scored highly in terms of openness, conscientiousness and agreeableness, and low on neuroticism, were more likely to report having better relationships with their siblings. Finally, in a qualitative study, Roos et al (2019) found that perceptions of grandparents' personality (e.g., empathetic vs. rigid) influenced whether young adult women desired closeness with, or distance from, their grandparents.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Relatively few studies have examined grandchild-grandparent relationship quality in the context of familial emotional support provision over the transition to adulthood. Studies have found that the level of closeness in grandparents' relationships with their young adult grandchildren is associated with: the closeness of parents' (particularly mothers) relationships with both the grandparents and the young adults (Monserud, 2008); physical proximity to grandparents (Roos et al, 2019;Wise and Onol, 2020); grandparent gender -with closer relationships typically found with grandmothers (Wise and Onol, 2020); contact frequency, medium, and quality (Wise and Onol, 2020); and the level of affectionate communication by grandparents (Mansson et al, 2017).…”
Section: Family Relationship Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…An interviewee or FP who sits too close, asks personal questions, or provides inappropriate information, indicates an emotional distance which is uncomfortably close. Conversely, adopting a closed posture, avoiding eye contact and providing short answers or questions would indicate a lack of trust (Roos et al, 2019).…”
Section: Emotional Distancementioning
confidence: 99%